2010
DOI: 10.1590/s0004-282x2010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral brain edema in intracranial meningiomas

Abstract: Occurrence of peritumoral brain edema (PBE) in meningiomas has been associated with several factors in recent years, although its pathophysiological mechanism has not yet been fully elucidated. The aim of this study was to analyze the correlation between the presence / degree of PBE and factors such as gender, age, size and histological subtype of tumor. We analyzed the MRI images of 74 patients operated on Hospital Beneficência Portuguesa de Porto Alegre for the presence / degree of PBE and data was statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…PTBE is a well-known negative prognostic factor as it can exacerbate preoperative neurological deficits, increase the risk of intra-operative complications, and prolong hospitalization time; however, its pathophysiology is yet unclear. Factors like tumor size and histological type, location, and gender have been proposed to relate with PTBE, even in cases of small, peripheral, low malignancy meningiomas (Lee et al 2008 ; Pereira-Filho 2010 ). The implication of E-cadherin, beta catenin (Rutkowski et al 2018 ), and hypoxia inducible factor-1 (HIF-1) (Reszec et al 2013 ) along with the vascular endothelial growth factor A (VEGF-A) pathway activation and increased vascular supply (Nassehi et al 2011 ; Nassehi et al 2013 ; Sakuma et al 2008 ; Schmid et al 2010 ) support the theory that PTBE in meningiomas is vasogenic, e.g., a growing meningioma, results in a further increase of intratumoral venous pressure leading to tumor congestion and accumulation of angiogenic substances, increased permeability of cerebral-pial capillaries and expansion of the PTBE (Hou et al 2013 ; Nassehi 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…PTBE is a well-known negative prognostic factor as it can exacerbate preoperative neurological deficits, increase the risk of intra-operative complications, and prolong hospitalization time; however, its pathophysiology is yet unclear. Factors like tumor size and histological type, location, and gender have been proposed to relate with PTBE, even in cases of small, peripheral, low malignancy meningiomas (Lee et al 2008 ; Pereira-Filho 2010 ). The implication of E-cadherin, beta catenin (Rutkowski et al 2018 ), and hypoxia inducible factor-1 (HIF-1) (Reszec et al 2013 ) along with the vascular endothelial growth factor A (VEGF-A) pathway activation and increased vascular supply (Nassehi et al 2011 ; Nassehi et al 2013 ; Sakuma et al 2008 ; Schmid et al 2010 ) support the theory that PTBE in meningiomas is vasogenic, e.g., a growing meningioma, results in a further increase of intratumoral venous pressure leading to tumor congestion and accumulation of angiogenic substances, increased permeability of cerebral-pial capillaries and expansion of the PTBE (Hou et al 2013 ; Nassehi 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis of PTBE in meningiomas is highly variable and multifactorial 20,21 . The mechanisms operating in edema genesis have not been completely elucidated 22‐25 . The expression of vascular permeability factor/vascular endothelial growth factor (VPF/VEGF) and its endothelial receptor “flt‐1” has been studied in MM by Christov et al, who reported that the density of vessels positive for VPF/VEGF/flt‐1 expression was much higher with MM than in other solid meningiomas, possibly ascribing it as a key role as a driver for microcyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean tumor volume was 27.81 cm 3 without significant differences between males and females. Some studies found no statistically significant correlation between tumor volume and PTBE ( 10 , 11 ), but some papers report on strong correlation between tumor volume and PTBE ( 6 , 8 ). Some tumors caused significant venous compression and ischemic stroke and significant brain edema ( 12 ).…”
Section: Discussionmentioning
confidence: 99%